(untitled) (International journal of artificial intelligence, 2025)
The AUS preposition is an important word in German that expresses location, action, and other states. The correct translation and use of this preposition in Uzbek varies depending on its context. During the learning process, students will learn more about the meaning and use of the AUS preposition to correctly understand actions and states occurring in German. This will also help improve their language skills.